2019
DOI: 10.6061/clinics/2019/e736
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sitagliptin added to metformin and insulin compared with voglibose in patients with newly diagnosed type 2 diabetes

Abstract: OBJECTIVE: To assess the efficacy and safety of sitagliptin compared with voglibose added to combined metformin and insulin in patients with newly diagnosed type 2 diabetes (T2DM). METHODS: In this 12-week prospective, randomized, parallel trial, 70 newly diagnosed T2DM patients with glycosylated hemoglobin (HbA1c) ≥9% and/or fasting plasma glucose (FPG) ≥11.1 mmol/L were randomized (1:1) to receive sitagliptin 100 mg per day + metformin + insulin glargine or voglibose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The Fig. 2(a) reflects the blood glucose fasting graph of the drugs effect on clinical data after 26 weeks of sitagliptin (50mg) treatments [11]. This graph also clearly showing the considerable the effect on glycaemic control level.…”
Section: Discussionmentioning
confidence: 89%
“…The Fig. 2(a) reflects the blood glucose fasting graph of the drugs effect on clinical data after 26 weeks of sitagliptin (50mg) treatments [11]. This graph also clearly showing the considerable the effect on glycaemic control level.…”
Section: Discussionmentioning
confidence: 89%
“…In this meta-analysis, we retrieved 40 relevant studies from the three databases; MEDLINE, CENTRAL, and Ichushi-web, as shown in the flowchart ( Fig 1 ). Among these studies, data for analysis were available for six of seven DPP-4 inhibitors: alogliptin (n = 2) [ 29 , 30 ], anagliptin (n = 1) [ 31 ], linagliptin (n = 3) [ 32 34 ], saxagliptin (n = 4) [ 35 38 ], sitagliptin (n = 26) [ 39 64 ], and vildagliptin (n = 4) [ 65 68 ], but not for teneligliptin (n = 0). Comparators of DPP-4 inhibitors were α-GIs (n = 9) [ 30 , 31 , 34 , 35 , 41 , 50 , 63 65 ], GLP-1 analogues (n = 5) [ 47 , 52 , 58 , 62 , 68 ], metformin (n = 5) [ 29 , 38 40 , 56 ], SGLT2 inhibitors (n = 5) [ 36 , 53 , 54 , 60 , 61 ], sulfonylureas (n = 12) [ 32 , 33 , 37 , 43 46 , 48 , 57 , 59 , 66 , 67 ], and thiazolidinediones (n = 4) [ 42 , 49 , 51 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that DPP-4 inhibitors are superior to α-GIs but inferior to GLP-1 analogues in terms of beta-cell preserving effect. In our meta-analysis between DPP-4 inhibitors and α-GIs using all the retrieved articles, we included a study in which all participants were given insulin [64]. Nevertheless, removal of that study [64] from meta-analysis did not change the statistical results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DPP4 inhibitors enhance glucagon-like peptide-1 and glucose-dependent insulin-tropic polypeptide which leads to increased insulin secretion by β cells of the pancreas and reduced glucagon secretion which in turn lowers glucose production in the liver [19]. Add-on therapy of sitagliptin and vildagliptin is also safe and well-tolerated when combined with metformin [20][21][22].…”
Section: Introductionmentioning
confidence: 99%